Analisis Faktor-Faktor yang Mempengaruhi Pengungkapan Lingkungan pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Iskandar Itan; Jessy Jessy (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
The environment is something that needs to be considered by companies in carrying out their business activities. This study aims to analyze the factors that affect environmental disclosure in Indonesia in terms of sustainability reports published by companies. The study used 43 companies listed on the Indonesia Stock Exchange as the object of research for the period 2015-2019. The results of this study explain that listing age and independent audit have a significant positive effect on environmental disclosure, profitability and leverage do not have a significant effect on environmental disclosure, while company size has a significant negative effect on environmental disclosure.